2011
DOI: 10.1016/j.lpm.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

La vitamine D chez l’adulte : recommandations du GRIO

Abstract: Serum level of 25-(OH)-vitamin D is a reliable marker of vitamin D repletion and therefore medical management can be based on its evaluation at both an individual-and population-based level. In every situation when the therapeutic goal requires an optimal serum 25-(OH)-vitamin D level for an appropriate medical care, it is mandatory to measure baseline level in order to define loading and maintenance dosages of vitamin D supplementation. These situations include lack or very low sun exposure, falls, osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Serum 25(OH)D determination was performed using an electrochemiluminescence (Cobas E411 immunoassay analyzer, Sterifil, casablaca, Morocco) measuring a range of 3–100 ng/mL or 7.5–250 nmol/L. Based on the thresholds of 25(OH)D levels proposed by the Research Group on Information on Osteoporosis (GRIO) and adopted by the Moroccan Society of Rheumatology to define a vitamin D deficiency or insufficiency, women were classified as sufficient (>30 ng/mL), insufficient (10 to 29.9 ng/mL), and deficient (<10 ng/mL) [ 80 , 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…Serum 25(OH)D determination was performed using an electrochemiluminescence (Cobas E411 immunoassay analyzer, Sterifil, casablaca, Morocco) measuring a range of 3–100 ng/mL or 7.5–250 nmol/L. Based on the thresholds of 25(OH)D levels proposed by the Research Group on Information on Osteoporosis (GRIO) and adopted by the Moroccan Society of Rheumatology to define a vitamin D deficiency or insufficiency, women were classified as sufficient (>30 ng/mL), insufficient (10 to 29.9 ng/mL), and deficient (<10 ng/mL) [ 80 , 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…The status of vitamin D was evaluated by serum 25(OH)D concentrations measurement and classified as per French ORIG guidelines (deficient: <25 nmol/L (<10 µ g/L), insufficient: 25-75 nmol/L (10-30 µg/L) and sufficient: ≥75 nmol/L (≥30 µg/L)) [21,27]. Two different time points were selected: (i) up to three months before the SARS-CoV-2 infection onset (T1), and (ii) during the first week of hospitalisation (T2).…”
Section: Serum Concentrations Of 25(oh)d and Vitamin D Statusmentioning
confidence: 99%
“…Moreover, the analysis of an elderly or even very elderly population, which is rarely represented in the literature, also makes our work interesting. To our knowledge, only one study has looked at the impact of pre-hospitalization supplementation in the very elderly [27]. As previously mentioned, the population of our study is representative of patients hospitalised for COVID-19 and of patients presenting severe forms of the disease during the first wave of the COVID-19 pandemic.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…Vitamin D deficiency affects more than one billion people at all stages of life worldwide [6]. It occurs most in the elderly, smokers, obese individuals and patients with chronic diseases such as diabetes mellitus, hypertension, and various gastrointestinal diseases [7]. In the last decade, several studies have shown a potential link between vitamin D deficiency and various diseases, especially systemic infections [8].…”
Section: Introductionmentioning
confidence: 99%